What can we learn from retracted studies in the nursing field in the last 20 years? Findings from a scoping review: Article retractions in nursing - Joaquim, Silvania; Longhini, Jessica; Palese, Alvisa (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work: Literature reviews have summarised the number of retracted studies and guidelines have been developed to prevent this issue. However, available data are scarce in the nursing field. Learning from other experiences may be able to increase awareness of the issue and prevent avoidable errors. Therefore, the intent of this study was to map retracted articles in the nursing field by investigating the reasons for retractions in order to elicit strategies to prevent their occurrence.Methods: A scoping review was performed by searching PubMed and Cumulative Index to Nursing and Allied Health (CINAHL) for articles published from 2001 to 2021. Quantitative primary and secondary studies related to the nursing field and written in English, with a “retracted article” message and/or presenting a retraction notice, have been included. The main reasons for retraction have been recorded, as well as the main features of the studies retracted.Results: Out of 274 studies, we detected 26 retractions, of which eight were literature reviews and seven were experimental studies. Editors were the most frequent party requiring retraction. The retracted studies originated from 11 countries and were mostly published (n = 19) in general nursing journals. Scientific misconduct was the main cause of retraction (n = 18), while the remaining retractions were due to other types of errors.Conclusions: Most of the study retractions were issued by editors and originated mostly from high-scientific output countries. Scientific misconduct represented the principal cause of retraction; from these failures, educational strategies have been identified in order to prevent issues and to increase awareness among researchers and healthcare professionals.